MURAL: MEDIA KREATIVITAS MEMPERINDAH DINDING SEKOLAH SDN BABAKAN RADEN 01 CARIU BOGOR JAWA BARAT - Kusuma, Heru Budi; Andreas; Benedict, Justin Owen (Jurnal Bakti Masyarakat Indonesia, 2024)
A mural is a work of art created on the surface of a wall or wall using various media, such as paint, markers, or other suitable materials. Blank, monotonous walls can be transformed into eye-catching works of art and liven things up. Our partner in this PKM activity is SDN Babakan Raden 01 Cariu, Palasari Village, Sukajadi Village, Cariu District, Bogor Regency, West Java Province. From the results of observations, it was discovered that Mitra had an empty wall on the side of the school building which looked dirty because the paint on the walls was peeling, making it unsightly. The partners have long had the desire to process the empty wall by drawing on it so that it looks clean and beautiful. The activity of creating mural works can be carried out as a community service activity carried out by lecturers at the Faculty of Fine Arts and Design, Tarumanagara University. Lecturers who have a background in fine arts and design education are expected to be able to provide scientific contributions to teachers through this program which is tailored to teaching needs at the elementary school level. The approach method in this community service program is practically applicable. The point is to apply the students' skills in drawing or painting that they acquired during college. Practical means direct practice in the field. The main characteristic of mural-making activities is the emphasis on a creative process that involves exploration, problem solving, and critical thinking, as well as providing space for students to express themselves freely. The output resulting from the activity of creating mural works is an article that will be published in the National Journal and a module for creating mural works whose copyright is registered. ABSTRAK Mural adalah sebuah karya seni yang dibuat di atas permukaan dinding atau tembok menggunakan berbagai media, seperti cat, spidol, atau bahan-bahan lain yang sesuai. Dinding yang kosong dan monoton dapat diubah menjadi karya seni yang menarik dan menghidupkan suasana. Mitra kami dalam kegiatan PKM ini adalah SDN Babakan Raden 01 Cariu, Kampung Palasari, Desa Sukajadi, Kecamatan Cariu, Kabupaten Bogor, Provinsi Jawa Barat. Dari hasil observasi, diketahui bahwa mitra memiliki dinding kosong di bagian sisi Gedung sekolah yang sudah tampak kumuh karena cat dindingnya sudah mengelupas sehingga kurang sedap dipandang. Pihak mitra sudah lama memiliki keinginan untuk mengolah dinding kosong tersebut dengan menggambarnya agar terlihat bersih dan indah. Kegiatan membuat karya mural dapat dilaksanakan sebagai kegiatan pengabdian kepada masyarakat yang dilakukan oleh dosen Fakultas Seni Rupa dan Desain Universitas Tarumanagara. Dosen-dosen yang memiliki latar pendidikan seni rupa dan desain diharapkan dapat memberikan kontribusi keilmuan kepada para guru melalui program tersebut yang disesuaikan dengan kebutuhan pengajaran di tingkat sekolah dasar. Metode pendekatan dalam program abdimas ini adalah aplikatif praktis. Maksudnya adalah mengaplikasikan keahlian mahasiswa dalam menggambar atau melukis yang diperolehnya di masa kuliah. Praktis maksudnya adalah praktek langsung di lapangan. Karakteristik utama dari kegiatan membuat mural adalah penekanan pada proses kreatif yang melibatkan eksplorasi, pemecahan masalah, dan pemikiran kritis, serta memberikan ruang bagi siswa untuk mengungkapkan diri secara bebas. Luaran yang dihasilkan dari kegiatan membuat karya mural adalah artikel yang akan dipublikasikan di Jurnal Nasional dan Modul membuat karya mural yang didaftarkan hak ciptanya